Domicide : the global destruction of home - Porteous, J. Douglas (John Douglas), 1943- (McGill-Queen's University Press, 2001)
"Media reports describing the destruction of people's homes, for reasons ranging from ethnic persecution to the perceived need for a new airport or highway, are all too familiar. The planned destruction of homes affects millions of people globally; places destroyed range in scale from single dwellings to entire homelands. Domicide tells how and why the powerful destroy homes that happen to be in the way of corporate, political, bureaucratic, and strategic projects. Too frequently, this destruction is justified as being in the public interest." "Douglas Porteous and Sandra Smith begin their analysis by examining just how important home is to human life and community. Using a multitude of case studies of displacement, they derive a theoretical framework that addresses the motives for, methods, and effects of domicide. Two case studies of resettlement resulting from hydro-electric power development in British Columbia are used to test this framework. Porteous and Smith assess the implications of loss of home, evaluate current efforts at mitigation, suggest better policies to alleviate the suffering of the dispossessed, and - as a last resort - urge resistance against unacceptable projects."--Jacket